Synthesis and Aqueous Solution Properties of Block Copolyethers with Latent Chemical Functionality. Issue 21 (29th August 2016) - Stoyanova, Boyana; Novakov, Christo; Tsvetanov, Christo B.; Rangelov, Stanislav
Abstract : Three series of polyglycidol‐poly(allyl glycidyl ether)‐polyglycidol (PG‐PAGE‐PG) triblock copolymers with ranging PG contents and fixed molar masses of the middle PAGE block are prepared. The copolymers are analogous to the Pluronic, poly(ethylene oxide)‐poly(propylene oxide)‐poly(ethylene oxide) (PEO‐PPO‐PEO), block copolymers in which the chemically inert PEO and PPO are substituted by PG and PAGE, respectively, exhibiting latent chemical functionality. They are prepared by solvent‐free sequential anionic polymerization of allyl glycidyl ether and ethoxyethyl glycidyl ether followed by cleavage of the protective groups. In aqueous solution the block copolymers self‐associate. According to the thermodynamic data, the self‐association is enthalpically favored with a small entropy contribution, which is fundamentally different from that of Pluronic block copolymers. The nanostructures are parameterized by dynamic and static light scattering and visualized by transmission electron microscopy. Data indicate formation of relatively large particles that are identified as compound particles held together by strong hydrogen bonding promoted by the numerous hydroxyl groups from the PG moieties. Abstract : Polyglycidol‐poly(allyl glycidyl ether)‐polyglycidol (PG‐PAGE‐PG) triblock copolymers are prepared by solvent‐free sequential anionic polymerization. They are considered as analogs of the Pluronic copolymers in which the chemically inert poly(ethylene oxide) and poly(propylene oxide) are substituted by PG and PAGE, which exhibit latent chemical functionality. In aqueous solution they self‐associate into large particles via fundamentally different mechanism from that of their analogs.